Nut culture - Pierce, John Martin (My University, 1898)
Introduction: Until recently, the world has depended chiefly upon the wild trees for its supply of nuts. They were never used as a staple article of food, but were merely incidental features in our living. It is probably for this reason that nuts have never been cultivated. We are not impelled by necessity to plant and rear such trees as hickory and walnut, even though we may like their fruit. Our forests are rapidly disappearing and there is liable to be a time soon, when nuts must be raised in our orchards, if we are to have any at all. The edible nuts, though they never have been so used, may profitably be made staple articles of food. They have a high nutritive value, and could well take the place of some of the other foods. If more of the natural products of the earth were eaten and less of artificially prepared and adulterated articles, mankind would be much the better for it.
Citation: Pierce, John Martin. Nut culture. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Trees; Nuts; Forests; Earth; Theses; Manuscripts (documents)